ChemInform Abstract: KH2PO4 Promoted Practical and Environmentally Friendly Preparation of Coumarin‐3‐carboxylic Acids under Solvent‐Free Condition. Issue 52 (6th December 2016) - Lv, Chengwei; Gao, Shuangqiu; Xiao, Di; Yang, Ying; Wei, Xiaoyue; Sun, Sai; Lang, Jian
Abstract: A green Knoevenagel‐intramolecular cyclization cascade reaction of Meldrum′s acid with ortho‐hydroxybenzaldehydes affords 3‐coumarincarboxylic acids in good to high yields.